SISTEM PENGENDALIAN INTERN DALAM UPAYA MENCEGAH TERJADINYA KREDIT MACET PADA PT. BANK RAKYAT INDONESIA (PERSERO). Tbk KANTOR CABANG SINJAI - Amir Amir; Andi Ika Nurfika (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This study aims to determine the internal control system in an effort to prevent the occurrence of bad loans at PT. Bank Rakyat Indonesia (Persero). Tbk Branch Office of Sinjai. The method of analysis used in this research is descriptive analysis method. The method of analysis by first collecting existing data and then clarified, analyzed and interpreted so as to provide a clear picture of the circumstances under study. The results showed that the internal control system in the effort to prevent the occurrence of bad debts at the Indonesian people's bank (Persero) Tbk Branch Office Sinjai through the stages of internal control, the environment control, risk assessment, control activities, information and communication and monitoring / monitoring has been running very effective. This is evident from all the shared questionnaires. From 19 questions on 20 respondents there are 98% yes and 2% answer no answer. And from the collectibility report for the loan for a year showed 0.93% who experienced bad credit. Which means the level of bad debts at Bank Rakyat Indonesia (Persero) Tbk Branch Office Sinjai classified as low because the standard of BI maximum 5%